Performance Characteristics and Nutrient Utilization of Starter Broilers Fed Raw and Processed Pigeon Pea (Cajanus cajan) Seed Meal - Onu, P.N.; Okongwu, S.N. (International Journal of Poultry Science, 2006)
A 28 - day feeding trial was conducted to evaluate the effect of processing of pigeon pea seeds on the performance and nutrient digestibility of finisher broilers. Four experimental diets were formulated such that each diet contained raw, boiled, boiled with potash and toasted pigeon pea seed meals at 26% dietary level respectively. One hundred and ninety two 5-week old Anak 2000 broiler chicks were randomly assigned to the four experimental diets in a completely randomized design (CRD). Each treatment group was replicated four times with 12 birds per replicate. At the end of the 4 weeks feeding trial, three birds were randomly selected from each replicate and transferred to metabolic cages for faecal collection and determination of apparent nutrient digestibility. Another set of 3 birds were randomly selected from each replicate, deprived of water but not feed for 24 hours, slaughtered and eviscerated for organ weight determination. Results showed significant (P < 0.05) differences in performance among the birds fed processed and raw pigeon pea seed meals. Birds fed processed pigeon pea seed meal performed significantly (P < 0.05) better than those on raw pigeon pea seed meal. There was no significant (P > 0.05) difference in performance among the groups fed differently processed pigeon pea seed meals. The results of the digestibility trial showed that significant (P < 0.05) differences existed among the groups in protein digestibility only. The results of the trial indicated that the three processing methods boiling, boiling with potash and toasting were effective in reducing the antinutritional factors in pigeon pea seeds. The result of the study also indicated improved nutritive value of pigeon pea boiled with potash.